Movement of water in concrete incorporating air-phase - Sharma, Anil; Maekawa, Koichi; Pichai Nimityongskul; Yamaguchi, Hiroki; Government of Japan (Bangkok : Asian Institute of Technology, 1991)
The longevity and durability of concrete remain a continuing a rea of research activity a nd thought . The process of deterioration of concrete is mediated largely by water . I n this research the movement of water in the capi11ary pore s paces of concrete was studied indifferent conditions . In the present study key is the consideration of multi - phase or Gas-Liquid movement, liquid phase movement is associated with the gas phase. Water plays a dual role in corrosion phenomenon. It acts as the carrier medium for some elements of corrosion like Cl- in its liquid phase , o n t he other ha nd it prevents the passage of other elements like o2. For corrosion of steel lying just below t he cover concrete , the alternate wetting a nd drying cycle is very dangerous as he r e the ingress of elements of corrosion can take place . In this study the movement of water in the wet tingcycle was considered mainly in t he concrete of various mix proport ions. Here water moves as a liquid in the capillary pore spaces of concrete, driven by t he forces of surface tension, pressure gradient and is resisted by t he friction between wat e r and concrete. The effect of water/cement ratio , absorption pressure , length of specimen, curing age , initial conditions , bleeding , and gravity on the water movement was studied . In the field structures, deterioration level s are different in bridge deck like structures a nd column structures. I n this study, for a l 1 the tests two boundary conditions A a nd B we reused, simulating the field situation in above two types of structures. Boundary conditions are related to the movement of the air phase. In boundary condition A, since the top face is open so gas phase movement is free, as water comes in t he capillary pore spaces air escapes from t he top. In boundary condition B, since top face is sea led so gas phase movement is stopped. As water movement occurs , space available to air reduces a nd a pressure 4 Pa is applied on t he incoming water . Specimens with boundary condition A showed larger moisture absorption than ones with boundary condition B. The effect of boundary conditions is more prominent in longer specimens and in specimens made with mortar concrete of larger W/C ratio . General formulation for multi - phase water movement in concrete is presented. A mode l is developed considering the equilibrium of forces, for the liquid water movement drive n by surface tension and pressure a nd resisted by the s hear friction be tween wat e r a nd concrete . Results obtained from the mode l were compared with experimental results a nd they s how very good agreement .
A thesis submitted in partial fulfillment of t he requirement for the degree of master of engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Concrete -- Permeability